Assessment of Risk Factors Associated with Increased Incidence of Thalassemia in Najaf Governorate - Sarah Abbood Shanan; Haidar Sahib Sharad; Noor Hadi Hassan (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Thalassemia is a common inherited hemoglobin disorder characterized by defective globin chain synthesis and widespread global distribution. Specific Background: The prevalence of thalassemia varies across regions and is influenced by demographic and hereditary factors, particularly in Middle Eastern populations. Knowledge Gap: Limited localized evidence exists regarding the specific risk factors contributing to thalassemia incidence in Najaf Governorate. Aims: This study aimed to identify demographic and genetic risk factors associated with increased thalassemia cases in Najaf. Results: A cross-sectional study of 167 patients revealed higher prevalence among males, children aged 1–10 years, and urban residents. Blood group O was most common, while Rh-positive status reflected general population trends. Parental consanguinity and positive family history showed strong associations with disease occurrence, and thalassemia major was more prevalent than minor forms. Novelty: This study provides localized epidemiological evidence highlighting the combined role of demographic and hereditary determinants in thalassemia distribution. Implications: The findings emphasize the importance of premarital screening, early diagnosis, and community awareness programs to reduce disease burden and improve health outcomes. Keywords: Thalassemia, Risk factors, Consanguinity, Epidemiology, Najaf Key Findings Highlights Higher cases observed in early childhood and urban populations Strong association between parental relatedness and disease occurrence Familial clustering evident through multiple affected siblings